Mourning, Memorials, and Filmic Traces: Reinscribing the "Corps strangers" and Unknown Soldiers in Bertrand Tavernier's Films - Panivong Norindr (Studies in 20th & 21st Century Literature, 1999)
The tirailleurs indigènes, as cinematic figures, occupy an ex-centric place in contemporary French cinema...
Keywords: tirailleurs indigènes; ex-centric; contemporary French cinema; Mourning; Memorials; Filmic Traces